Valorization of sweet bananas (Musa sinensis) by drying after osmotic dehydration - AHOUANNOU, CLÉMENT; AMOUSSOU, Balbine; mahamat, Seid Ali; TOUGAN, P. ULBAD; SOUMANOU, MANSOUROU MOHAMED; TCHOBO, PAUL FIDÈLE (My University, 2017)
The aim of the current study was to identify the suitable treatment mode for the preservation of sweet bananas (Musa sinensis) by drying after osmotic dehydration. Therefore, banana samples of 1cm of thickness were dehydrated with different sugar solutions with or without salt at three different temperatures (25°C, 45°C and 60°C) and the greatest water losses were subjected to air drying at 45 and 60°C. It comes out from the survey that the best dehydrations were observed for the solutions binary of saccharose at 50 °Brix and ternary of saccharose at 50 °Brix and NaCl (5 %) with water losses of more than 30%. After drying, the results obtained for ash, vitamin C, color and texture showed that the samples dehydrated before drying as well as possible preserve more the nutritional and physical qualities of banana.
Keywords: Osmotic dehydration; quality; drying; Musa sinensis.